High-stability steel slag cement concrete and preparation method thereof

CN122914342APending Publication Date: 2026-10-16XINJIANG PROD & CONSTR CORPS HIGHWAY SCI & TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611206257.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

本发明将振动成型、梯度养护和界面强化工艺参数进行耦合优化,消除钢渣水泥混凝土的膨胀风险,消除内部应力,避免诱发为裂纹,增强界面结合力,提高抗渗性,降低氯离子渗透速率,从而提升钢渣水泥混凝土质量,同时提出短期加速试验和长期预测模型的双重验证体系,为其验收提供量化依据。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122914342A_ABST
    Figure CN122914342A_ABST
Patent Text Reader

Abstract

The application discloses a kind of high-stability steel slag cement concrete and preparation method thereof, it is related to civil engineering material technical field, including: step 1: raw material control, including coarse aggregate screening, fine aggregate modification and gel material compounding;Step 2: gradient curing, including gradient temperature control and stress release;Step 3: interface strengthening, including nano modification and chemical bonding;Step 4: detection acceptance, including short-term accelerated test and long-term prediction model dual verification.The application couples and optimizes vibration forming, gradient curing and interface strengthening process parameters, eliminates the expansion risk of steel slag cement concrete, eliminates internal stress, avoids inducing crack, enhances interface bonding force, improves impermeability, reduces chloride ion penetration rate, thereby improves steel slag cement concrete quality, while proposing short-term accelerated test and long-term prediction model dual verification system, to provide quantitative basis for its acceptance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of civil engineering materials technology, and in particular to a highly stable steel slag cement concrete and its preparation method. Background Technology

[0002] Steel slag, a solid waste generated in the metallurgical industry, is one of the important raw materials for preparing steel slag cement concrete. By expanding and improving the process of preparing high-quality steel slag cement concrete from solid waste steel slag, the recycling rate of solid waste steel slag from the metallurgical industry can be effectively improved.

[0003] The quality of steel slag cement concrete prepared today is not high, mainly due to the following reasons: Traditional autoclaving tests (GB / T24175) only simulate a single high-temperature and high-pressure environment and do not consider the effects of wet-dry cycles / freeze-thaw coupling, resulting in the expansion rate of components exceeding 0.3% after 2 years of service (industry standard ≤0.1%). Gradient curing requires segmented temperature control (50℃→80℃), but the temperature control accuracy of the existing production line is ±3℃, which can easily cause temperature gradient stress. The porosity of the transition zone (ITZZ) between steel slag particles and cement paste is relatively large, generally greater than 12%, which leads to a decrease in the impermeability of the prepared steel slag cement concrete and an increase in the chloride ion penetration rate. The lack of a standard testing method for the long-term expansion rate of steel slag concrete makes it difficult to control the quality of steel slag concrete due to the lack of a basis for project acceptance.

[0004] To address the aforementioned deficiencies, a highly stable steel slag cement concrete and its preparation method are proposed. Summary of the Invention

[0005] The purpose of this invention is to provide a highly stable steel slag cement concrete and its preparation method, so as to solve the problems mentioned in the background art.

[0006] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing highly stable steel slag cement concrete, comprising: Step 1: Raw material control, including screening of coarse aggregates, modification of fine aggregates, and compounding of gel materials; Step 2: Gradient curing, including gradient temperature control and stress release; Step 3: Interface strengthening, including nano-modification and chemical bonding; Step 4: Testing and acceptance, including dual verification of short-term accelerated testing and long-term prediction models.

[0007] Preferably, in step 1, the coarse aggregate screening specifically includes: Steel slag coarse aggregate was taken and subjected to autoclaving test to obtain steel slag coarse aggregate with a pulverization rate of less than or equal to 3.0%; Boiling tests were then conducted on steel slag coarse aggregate with a pulverization rate of less than or equal to 3.0% to obtain steel slag coarse aggregate with an expansion rate of less than or equal to 0.80%.

[0008] Preferably, the autoclaving test specifically involves placing the steel slag coarse aggregate in a high-temperature and high-pressure environment of 216℃ / 2MPa for three hours for autoclaving. The boiling test specifically involves boiling continuously in water at 100°C for five hours.

[0009] Preferably, in step 1, the fine aggregate modification specifically includes: The fine aggregate of steel slag was soaked in a 1.5% silane coupling agent ethanol solution for two hours; The soaked steel slag fine aggregate was then dried at 60°C to reduce the interfacial energy of the steel slag fine aggregate by 30%.

[0010] Preferably, in step 1, the gel material compounding specifically includes: Mix steel slag powder and blast furnace slag powder in a ratio of 3:7; The mixed steel slag powder and slag powder are then ground in a vertical mill until the specific surface area is greater than or equal to 600 m² / kg, and the activity index is not less than 95%.

[0011] Preferably, in step 2, the gradient temperature control specifically includes: The formed steel slag cement concrete was placed in the curing chamber and left to stand for two hours. Then raise the temperature to 50℃ at a rate of ≤10℃ / h and keep it at that temperature for six hours; Then, the temperature is increased to 80℃ at a rate of ≤5℃ / h and kept at a constant temperature for twelve hours; Finally, the temperature is allowed to cool naturally to room temperature, with a cooling rate of <5℃ / h.

[0012] Preferably, in step 2, stress relief specifically includes: A honeycomb polyurethane elastic support frame is installed at the bottom of the curing chamber to support the steel slag cement concrete, wherein the compression rate of the honeycomb polyurethane elastic support frame is greater than 40%. The internal thermal stress of steel slag cement concrete is eliminated by a vibration molding process with a frequency of 50 Hz and an amplitude of 0.5 mm.

[0013] Preferably, in step 3, the nano-modification specifically involves: incorporating 2% nano-silica into the concrete mixing stage and mixing it evenly with other gel materials; The chemical bonding specifically involves pretreating the surface of steel slag aggregate with a silane coupling agent to form a Si-O-Si covalent bond network with nano-silica, so that the pore area ratio of the interface transition zone is less than or equal to 8%.

[0014] Preferably, in step 4, the inspection and acceptance specifically includes: Based on the hydration kinetics of free calcium oxide and magnesium oxide in steel slag, a correlation equation between accelerated testing and long-term expansion was established: ; In the formula, Et represents the expansion rate of steel slag cement concrete at age t, E0 represents the ultimate expansion rate, and k represents the rate constant. The ultimate expansion rate E0 of the steel slag concrete sample was determined by the 28-day autoclaving-boiling combined test method. The value of the reaction rate constant k is calculated based on the free calcium oxide content of the steel slag; Substituting the limiting expansion rate E0 and the reaction rate constant k into the correlation equation, the two-year expansion rate of steel slag cement concrete is obtained.

[0015] On the other hand, the present invention also provides a method for preparing high-stability steel slag cement concrete, wherein the steel slag cement concrete is prepared by applying any one of the above-described methods for preparing high-stability steel slag cement concrete.

[0016] The technical effects and advantages of this invention are as follows: This invention couples and optimizes the process parameters of vibration molding, gradient curing, and interface strengthening to eliminate the expansion risk of steel slag cement concrete, eliminate internal stress, avoid inducing cracks, enhance interfacial bonding, improve impermeability, and reduce chloride ion penetration rate, thereby improving the quality of steel slag cement concrete. At the same time, it proposes a dual verification system of short-term accelerated testing and long-term prediction model to provide quantitative basis for its acceptance.

[0017] This invention employs a combined steam pressure and boiling method to screen steel slag, establishes an "expansion rate-age" prediction model, provides a standard for raw material screening, reduces the risk of expansion, and improves the durability of steel slag cement concrete.

[0018] This invention, by employing quantitatively controlled gradient heating curing combined with vibration molding, helps to eliminate internal stress in steel slag cement concrete and reduce the occurrence of cracks.

[0019] This invention employs the synergistic combination of steel slag and slag powder, utilizing nano-silica to achieve interface modification, reducing the porosity of the transition zone between steel slag particles and cement paste, and improving the impermeability of steel slag cement concrete.

[0020] This invention breaks through the limitations of traditional single pressure steam test by using dual detection indicators of short-term boiling expansion rate and long-term accelerated expansion rate prediction. It achieves accurate prediction of two-year expansion rate by 28-day accelerated test, providing quantitative basis for project acceptance. Attached Figure Description

[0021] Figure 1 This is a flowchart of the method of the present invention.

[0022] Figure 2 This is a schematic diagram of the steel slag component distribution of the present invention. Detailed Implementation

[0023] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0024] This invention provides, for example Figures 1-2 The method for preparing highly stable steel slag cement concrete shown includes: Step 1: Raw material control, including coarse aggregate screening, fine aggregate modification, and gel material compounding; in this embodiment, such as Figure 2 As shown, the main components of steel slag, by mass fraction, are 65% coarse aggregate, 25% fine aggregate, and 10% steel slag powder; the particle size of the coarse aggregate is between 4.75-31.5 mm, the particle size of the fine aggregate is less than 4.75 mm, and the particle size of the steel slag powder is less than 0.075 mm. Specifically, the screening of coarse aggregate includes: taking steel slag coarse aggregate and conducting a pressure steam test according to GB / T24175. The test process needs to be carried out in a high temperature and high pressure environment of 216℃ / 2MPa for three hours to obtain steel slag coarse aggregate with a pulverization rate of less than or equal to 3.0%. Then, the steel slag coarse aggregate with a pulverization rate of less than or equal to 3.0% is subjected to a boiling test according to the modified ASTM C151. The test process needs to be carried out in boiling water at 100℃ for five hours to obtain steel slag coarse aggregate with an expansion rate of less than or equal to 0.80%. The specific modification of fine aggregates includes: immersing steel slag fine aggregates in a 1.5% silane coupling agent (KH-570) ethanol solution for two hours, and then drying the immersed steel slag fine aggregates in a constant temperature environment of 60℃, thereby reducing the interfacial energy of the steel slag fine aggregates by 30%. The specific formulation of the gel material includes: mixing steel slag powder and slag powder in a ratio of 3:7, and then grinding the mixed steel slag powder and slag powder in a vertical mill until the specific surface area is greater than or equal to 600 m² / kg, while the activity index is not less than 95%; Traditional autoclaving tests (GB / T24175) only simulate a single high-temperature and high-pressure environment and only control the autoclaving pulverization rate (≤3.0%), ignoring the boiling expansion rate (≤0.8% in traditional processes). Furthermore, they do not consider the effects of wet-dry cycles / freeze-thaw coupling, thus concealing the expansion risk. This results in steel slag cement concrete components having an expansion rate exceeding 0.3% after two years of service (industry standard ≤0.1%). This embodiment uses a combined autoclaving and boiling test to screen steel slag, establishing an "expansion rate-age" prediction model and implementing a dual-control system for steel slag raw materials. This effectively reduces the risk of excessive expansion rates in steel slag cement concrete in the later stages.

[0025] Step 2: Gradient curing, including gradient temperature control and stress release; specifically, gradient temperature control includes placing the formed steel slag cement concrete into a curing chamber and letting it stand for two hours, then raising the temperature to 50°C at a rate of ≤10°C / h and holding it at a constant temperature for six hours, which is curing stage one; immediately following, raising the temperature to 80°C at a rate of ≤5°C / h and holding it at a constant temperature for twelve hours, which is curing stage two; finally, allowing it to cool naturally to room temperature, with a cooling rate of <5°C / h, which is curing stage three. The total duration of the entire curing stage is generally 24 hours. The stress relief process specifically includes installing a honeycomb polyurethane elastic support frame at the bottom of the curing chamber to support the steel slag cement concrete. The honeycomb polyurethane elastic support frame has a compression rate of more than 40%, and the internal temperature difference stress of the steel slag cement concrete is eliminated by a vibration molding process with a frequency of 50Hz and an amplitude of 0.5mm. During the curing and stress release stage of steel slag cement concrete, the curing chamber system mainly consists of an intelligent temperature control chamber, an elastic support frame placed in the intelligent temperature control chamber, a steam generator, a data acquisition terminal, and a vibration molding module. The intelligent temperature control chamber is equipped with a PID temperature control module, the elastic support frame has a honeycomb polyurethane buffer layer with a compression ratio of >40%, the steam generator uses a variable frequency atomizing nozzle (atomizing particle size <50μm), and the data acquisition terminal is equipped with a wireless transmission module (LoRa protocol). Because traditional curing processes lack quantitative control over the gradient heating rate and have insufficient constant temperature time, they can easily lead to thermal stress concentration inside steel slag concrete, inducing microcracks. Therefore, this embodiment uses three-stage temperature control, a gradient heating from 50℃ to 80℃, a constant temperature of 12 hours, and a cooling rate of less than 5℃ / h. Combined with elastic support and vibration molding processes during curing, the temperature stress release rate can be ≥85%, effectively eliminating the problem of thermal stress concentration inside concrete and reducing the probability of microcracks in concrete.

[0026] Step 3: Interface strengthening, including nano-modification and chemical bonding; specifically, nano-modification involves adding 2% nano-silica (particle size 5-20nm) to other gelling materials during the concrete mixing stage, specifically after dry mixing and before adding water, to ensure uniform dispersion; the specific process is as follows: nano-silica is added during the dry mixing stage of concrete (i.e., when cement, steel slag powder, slag powder, and aggregates are mixed), and the mixer is continuously stirred at a high speed of ≥120rpm for at least three minutes to ensure uniform dispersion of nano-silica in the concrete, and then water is added for wet mixing; the incorporation of nano-silica fills the interfacial transition zone (ITZ) between steel slag particles and cement paste, reducing the porosity to below 8%; The chemical bonding process involves pretreating the surface of the steel slag aggregate with a silane coupling agent (KH-570) to form a Si-O-Si covalent network with nano-silica. This reduces the porosity of the ITZ while increasing the interfacial bonding strength by 30%. In this embodiment, the porosity determination method of the interface transition zone (ITZ) between the steel slag particles and the cement paste is as follows: a scanning electron microscope (SEM) combined with image analysis software (such as ImageJ) is used to perform porosity statistics on the interface transition zone (ITZ) of the hardened concrete sample. When the porosity area ratio of the interface transition zone (ITZ) in the SEM image is less than or equal to 8% (calculated by threshold segmentation), the porosity of the concrete sample is determined to meet the standard. This embodiment uses nano-silica modification and silane coupling agent (KH-570) to pretreat the surface of steel slag aggregate, which can reduce the porosity of the transition zone between steel slag particles and cement paste to below 8%, effectively improving the impermeability of concrete and reducing the chloride ion penetration rate.

[0027] Step 4: Testing and acceptance, including dual verification of short-term accelerated testing and long-term predictive models; specifically, this includes establishing the correlation equation between accelerated testing and long-term expansion based on the hydration kinetics of free calcium oxide and magnesium oxide in steel slag. In the formula, Et represents the expansion rate of steel slag cement concrete at age t years, E0 represents the ultimate expansion rate, and k represents the rate constant. The steel slag concrete samples were subjected to a short-term test using the 28-day autoclaving-boiling combined test method, and the 28-day ultimate expansion rate E0 (e.g., 0.08%) was measured. Based on the free calcium oxide content of the steel slag (e.g., 4.2%), calculate the value of the reaction rate constant k (corresponding to 0.18). Substituting the limiting expansion rate E0 and the reaction rate constant k into the correlation equation, the two-year expansion rate of steel slag cement concrete is obtained (for example, setting t to 2 years, E2 = 0.08% × (1 - e - 0.18 × 2) ≈ 0.082% (measured value 0.08%), error < 3%). A dual verification system of "short-term accelerated test (28 days) + long-term prediction model (2 years)" was established, filling the technical gap in the life cycle stability assessment of steel slag cement concrete, breaking through the limitations of traditional single autoclave test, and realizing accurate prediction of 2-year expansion rate by 28-day accelerated test, providing quantitative basis for project acceptance. The steel slag cement concrete preparation method provided in this embodiment has the following advantages: In terms of raw material control, a combined autoclaving and boiling method is used to screen steel slag, and a "expansion rate-age" prediction model is established. Regarding curing technology, precise control of the gradient heating rate within ±1℃ is achieved, while elastic support and vibration molding effectively eliminate internal stress in the concrete, preventing the formation of microcracks. In terms of the material system, steel slag powder and blast furnace slag powder (in a 3:7 ratio) are synergistically activated, and nano-silica is used for interface modification to improve interfacial bonding strength and reduce ITZ porosity. Regarding testing methods, a dual indicator of "boiling expansion rate + 2-year accelerated expansion rate" is established to provide quantitative basis for project acceptance.

[0028] A method for preparing highly stable steel slag cement concrete is disclosed, comprising steel slag cement concrete prepared by the method described in the above embodiments; a comparative experiment was conducted between the steel slag concrete prepared by the above method and steel slag cement concrete prepared by a traditional process, and the experimental results are shown in the table below:

[0029] As shown in the table above, the steel slag cement concrete prepared by the preparation method provided by this invention is superior to steel slag cement concrete prepared by traditional processes in terms of quality, durability, and economic cost. At the same time, the cyclic test from -40℃ to 80℃ was verified, and the number of freeze-thaw cycles was >600 (national standard 250 times), and carbon emissions were reduced by 32% (based on LCA analysis).

[0030] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing highly stable steel slag cement concrete, characterized in that, include: Step 1: Raw material control, including screening of coarse aggregates, modification of fine aggregates, and compounding of gel materials; Step 2: Gradient curing, including gradient temperature control and stress release; Step 3: Interface strengthening, including nano-modification and chemical bonding; Step 4: Testing and acceptance, including dual verification of short-term accelerated testing and long-term prediction models.

2. The high-stability steel slag cement concrete and its preparation method according to claim 1, characterized in that, In step 1, the coarse aggregate screening specifically includes: Steel slag coarse aggregate was taken and subjected to autoclaving test to obtain steel slag coarse aggregate with a pulverization rate of less than or equal to 3.0%; Boiling tests were then conducted on steel slag coarse aggregate with a pulverization rate of less than or equal to 3.0% to obtain steel slag coarse aggregate with an expansion rate of less than or equal to 0.80%.

3. The method for preparing high-stability steel slag cement concrete according to claim 2, characterized in that, The autoclaving test specifically involves placing the steel slag coarse aggregate in a high-temperature and high-pressure environment of 216℃ / 2MPa for three hours for autoclaving. The boiling test specifically involves boiling continuously in water at 100°C for five hours.

4. The method for preparing high-stability steel slag cement concrete according to claim 3, characterized in that, In step 1, the fine aggregate modification specifically includes: The fine aggregate of steel slag was soaked in a 1.5% silane coupling agent ethanol solution for two hours; The soaked steel slag fine aggregate was then dried at 60°C to reduce the interfacial energy of the steel slag fine aggregate by 30%.

5. The method for preparing high-stability steel slag cement concrete according to claim 4, characterized in that, In step 1, the gel material compounding specifically includes: Mix steel slag powder and blast furnace slag powder in a ratio of 3:7; The mixed steel slag powder and slag powder are then ground in a vertical mill until the specific surface area is greater than or equal to 600 m² / kg, and the activity index is not less than 95%.

6. The method for preparing high-stability steel slag cement concrete according to claim 1, characterized in that, In step 2, gradient temperature control specifically includes: The formed steel slag cement concrete was placed in the curing chamber and left to stand for two hours. Then raise the temperature to 50℃ at a rate of ≤10℃ / h and keep it at that temperature for six hours; Then, the temperature is increased to 80℃ at a rate of ≤5℃ / h and kept at a constant temperature for twelve hours; Finally, the temperature is allowed to cool naturally to room temperature, with a cooling rate of <5℃ / h.

7. The method for preparing high-stability steel slag cement concrete according to claim 6, characterized in that, In step 2, stress relief specifically includes: A honeycomb polyurethane elastic support frame is installed at the bottom of the curing chamber to support the steel slag cement concrete, wherein the compression rate of the honeycomb polyurethane elastic support frame is greater than 40%. The internal thermal stress of steel slag cement concrete is eliminated by a vibration molding process with a frequency of 50 Hz and an amplitude of 0.5 mm.

8. The method for preparing high-stability steel slag cement concrete according to claim 1, characterized in that, In step 3, the nano-modification specifically involves: incorporating 2% nano-silica into the concrete mixing stage and mixing it evenly with other gel materials; The chemical bonding specifically involves pretreating the surface of steel slag aggregate with a silane coupling agent to form a Si-O-Si covalent bond network with nano-silica, so that the pore area ratio of the interface transition zone is less than or equal to 8%.

9. The method for preparing high-stability steel slag cement concrete according to claim 1, characterized in that, In step 4, the inspection and acceptance process specifically includes: Based on the hydration kinetics of free calcium oxide and magnesium oxide in steel slag, a correlation equation between accelerated testing and long-term expansion was established: ; In the formula, Et represents the expansion rate of steel slag cement concrete at age t, E0 represents the ultimate expansion rate, and k represents the rate constant. The ultimate expansion rate E0 of the steel slag concrete sample was determined by the 28-day autoclaving-boiling combined test method. The value of the reaction rate constant k is calculated based on the free calcium oxide content of the steel slag; Substituting the limiting expansion rate E0 and the reaction rate constant k into the correlation equation, the two-year expansion rate of steel slag cement concrete is obtained.

10. A method for preparing highly stable steel slag cement concrete, characterized in that, Steel slag cement concrete prepared by the method for preparing high-stability steel slag cement concrete according to any one of claims 1-9.